Detecting seizure patterns in patients with Alzheimer's disease using long‐term EEG monitoring: A feasibility study: Neuropsychiatry and behavioral neurology/Dementia. (7th December 2020) - Musaeus, Christian Sandøe; Waldemar, Gunhild; Larsson, Henrik Bo Wiberg; Andersen, Birgitte Bo; Høgh, Peter; Kidmose, Preben; Hasselbalch, Steen Gregers; Fabricius, Martin; Tøpholm, Richard; Rank, Mike Lind; Kjær, Troels Wesenberg; Frederiksen, Kristian Steen
Abstract: Background: Seizure patterns as detected with electroencephalography (EEG) has been suggested to be frequent in patients with Alzheimer's disease. However, long‐term EEG monitoring to detect seizure patterns requires hospitalization for longer periods of time, which is both expensive and difficult for patients with Alzheimer's disease.In the current feasibility study, we investigated whether it was possible for patients with Alzheimer's disease to wear ear‐EEG for long‐term EEG monitoring of seizure patterns at home. Method: We recruited patients who met the criteria for Alzheimer's disease and had no previous history of epilepsy. Seizure patterns was assessed using long‐term EEG monitoring with ear‐EEG for 48 hours every three months for half a year. Furthermore, patients and relatives were instructed in the use of a seizure diary, which was used during the ear‐EEG recordings. Result: So far, we have recruited 9 patients with Alzheimer's disease, and all patients who underwent ear‐EEG monitoring have been able to wear the ear‐EEG for at least 24 hours including sleep. We are currently in the process of investigating whether the patients with Alzheimer's disease show seizure patterns as measured with ear‐EEG. Conclusion: Long‐term EEG monitoring using ear‐EEG seems to be feasible for measuring seizure patterns in patients with Alzheimer's disease. If any of the patients show seizure patterns using ear‐EEG, we will be able to treat with anti‐epileptic medication, which may improve their symptoms.